Genome-Wide Identification of NAC Transcription Factors and Their Functional Prediction of Abiotic Stress Response in Peanut - Li, Pengxiang; Peng, Zhenying; Xu, Pingli; Tang, Guiying; Ma, Changle; Zhu, Jieqiong; Shan, Lei; Wan, Shubo (Frontiers in Genetics, 2021)
The NAC transcription factor (TF) is one of the most significant TFs in plants and is widely involved in plant growth, development, and responses to biotic and abiotic stresses. To date, there are no systematic studies on the NAC family in peanuts. Herein, 132 AhNACs were identified from the genome of cultivated peanut, and they were classified into eight subgroups (I–VIII) based on phylogenetic relationships with Arabidopsis NAC proteins and their conserved motifs. These genes were unevenly scattered on all 20 chromosomes, among which 116 pairs of fragment duplication events and 1 pair of tandem duplications existed. Transcriptome analysis showed that many AhNAC genes responded to drought and abscisic acid (ABA) stresses, especially most of the members in groups IV, VII, and VIII, which were expressed at larger differential levels under polyethylene glycol (PEG) and/or ABA treatment in roots or leaves. Furthermore, 20 of them selected in response to PEG and ABA treatment were evaluated by quantitative real-time polymerase chain reaction. The results showed that these genes significantly responded to drought and ABA in roots and/or leaves. This study was helpful for guiding the functional characterization and improvement of drought-resistant germplasms in peanuts.